(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
The main tasks and activities of the FVV are mainly: development and implementation of state policy in the field of elimination of emergencies, protection of life and health of citizens, elimination of consequences and harm reduction in case of emergencies, organization and functioning of the State system for the prevention of emergencies and management of actions in such situations, Directing civil protection, coordinating the activities of ministries, departments, local government bodies is focused on targeted production and practices.